Intercalation of barium into monoclinic tungsten oxide nanoplates for enhanced photoelectrochemical water splitting - Kalanur, Shankara S.; Seo, Hyungtak (Chemical Engineering Journal, 2019)
Intercalating alkali earth metals into WO3 lattice is a promising strategy to tune its optical and electrical properties. However, hollow cubic tunnels present in monoclinic WO3 do not provide sufficient space for the diffusion and intercalation of large ions into its interstitial cavities. Therefore, a unique synthesis strategy is required to intercalate large ions into the monoclinic WO3 lattice without causing structural distortion or damage. In this study, a single-step hydrothermal method is proposed for the fabrication of barium-intercalated monoclinic WO3 thin films for efficient photoelectrochemical water splitting applications. The intercalation of barium into WO3 is achieved by the hydrothermal condensation of peroxopolytungstic acid solution. The proposed method yields hydrated orthorhombic WO3, which provides enough space in the hexagonal interstitial cavities between its [0 0 1] planes for the stable intercalation of barium. Subsequently, stable barium-intercalated monoclinic WO3 is obtained via reconstructive transformation without causing any significant structural distortion or damage. The intercalation of barium affects the preferential direction of crystal growth and the morphology of WO3. Furthermore, barium intercalation reduces the bandgap of WO3 and slightly increases its carrier density. As a result, higher photocurrent and incident photon-to-current efficiency values are achieved. Based on spectroscopic and electrochemical results, a probable band diagram of barium-intercalated WO3 is proposed. Importantly, the proposed method can be efficiently extended to fabricate monoclinic WO3 thin films intercalated with large alkali metal and alkali earth metal ions for various applications.
Keywords: Band edge position; Incident photon-to-current efficiencies; Interstitial cavities; Optical and electrical properties; Photoelectrochemical water splitting; Reconstructive transformation; Tungsten oxide; Water splitting; Band edge position; Barium; Interstitial cavities; Tungsten oxide; Water splitting